Use and Design of Peer Evaluations for Bonus Allocations - GRIEDER, MANUEL; SCHUHMACHER, KARL (Journal of Accounting Research, 2025)
ABSTRACT We conduct an experiment to investigate the use of peer evaluations for compensation purposes. Although organizations often rely on peer evaluations for incentive compensation, it is not well understood how peer feedback should be used and designed to ensure non‐distorted evaluations and motivate effort provision. We study peer evaluations in form of bonus allocation proposals, thereby enabling a quantifiable test of our hypothesis. We distinguish between discretionary use (i.e., allocation by the manager) and formulaic use (i.e., allocation by the team via the average) of self‐including and self‐excluding proposals. We find that, relative to self‐including proposals, self‐excluding proposals are less distorted, irrespective of use, but lead to more effort provision only under formulaic use. Under discretionary use, the benefits of self‐excluding proposals are offset, as managerial biases enter bonus allocations. In sum, our findings illustrate benefits of delegating bonus allocations to teams through formulaic use of self‐excluding peer evaluations and extend the understanding of how organizations can effectively incorporate peer evaluations into incentive compensation.